Semen cryopreservation in Piaractus mesopotamicus: the effect of different diluents and freezing equipment - Teodozia, Edna Raquel; Araújo, Mayara; Lopes, Júlia; Montenegro, Assis; Salmito-Vanderley, Carminda Sandra (Revista Ciência Agronômica, 2020)
Piaractus mesopotamicus (Holmberg, 1887) is a fish native to the Basin of the River Plate and which has great economic importance. In view of this, there has been interest in developing biotechnologies that aim to optimise reproduction in captivity. The aim of this study was to verify the effect of freezing the semen of the pacu using different diluents and freezing equipment. The semen, after pooling, was diluted in the proportion 1:3 (semen: diluent) in two different freezing media, resulting from combining 10% DMSO with Glucose 5% or with ACP-104; it was then cryopreserved in a Dry Shipper or programmable freezer (PF). The samples were later thawed and evaluated for sperm kinetics, membrane integrity and sperm morphology using the Computer Assisted Sperm Analyser (CASA). The data were submitted to ANOVA, and the mean values compared by F-test (P